Macrophages Celebrating 140 Years of Discovery - Kumar, Vijay (IntechOpen, 2022)
Macrophages were first discovered in 1882 when Elia Metchnikoff recognized them as important phagocytic cells that can engulf any foreign material, including fungal spores. This discovery has proved to be a milestone in establishing the field of innate immunity. Macrophages are still ruling the area after 140 years of their discovery. This book explores the diverse role of macrophages in vertebrate immunity, parasitic, bacterial, and viral infections, regeneration, inflammation, and neurological diseases.